Implementasi Media Balok Warna terhadap Kemampuan Mengenal Warna pada Anak Usia 3-4 Tahun di KB Adduriyah 3 - Rahmawati; Maimon Sumo (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The cognitive development of early childhood requires appropriate stimulation, one of which is through color recognition. Color block media serves as an educational tool that not only introduces various colors but also familiarizes children with geometric shapes, numerical concepts, and trains their thinking and memory skills. This study aims to implement color block media as an innovative learning method to effectively improve early childhood abilities in color recognition. Early childhood is a stage of exploration, where the learning process must be concrete, engaging, and enjoyable. Color block media combines visual and manipulative approaches that can foster curiosity and active involvement in the learning process. This learning-through-play activity encourages children to naturally identify, differentiate, and name colors. The study used a quantitative method with a pretest-posttest design to determine the effectiveness of the media. The research was conducted at KB Adduriyah 3 on October 29, 2024, and data analysis was performed using a t-test through SPSS 18 for Windows. The results showed a significance value (2-tailed) of 0.00. Since this value is smaller than the significance level (α = 0.05), the null hypothesis is rejected, and the alternative hypothesis is accepted. The results of the study demonstrate that color block media has a significant impact on improving children's color recognition skills. Additionally, the media also enhances children's active participation in learning activities. Therefore, color block media is highly recommended as a creative and effective learning strategy for educators and parents in supporting the cognitive development of early childhood.